Improving manual oxygen titration in preterm infants by training and guideline implementation - van Zanten, Henriëtte A. (Eur J Pediatr, 2016)
To study oxygen saturation (SpO(2)) targeting before and after training and guideline implementation of manual oxygen titration, two cohorts of preterm infants <30 weeks of gestation needing respiratory support and oxygen therapy were compared. The percentage of the time spent with SpO(2) within the target range (85–95%) was calculated (%SpO(2)-wtr). SpO(2) was collected every minute when oxygen is >21%. ABCs where oxygen therapy was given were identified and analyzed. After training and guideline implementation the %SpO(2)-wtr increased (median interquartile range (IQR)) 48.0 (19.6–63.9) % vs 61.9 (48.5–72.3) %; p < 0.005, with a decrease in the %SpO(2) > 95% (44.0 (27.8–66.2) % vs 30.8 (22.6–44.5) %; p < 0.05). There was no effect on the %SpO(2) < 85% (5.9 (2.8–7.9) % vs 6.2 (2.5–8) %; ns) and %SpO(2) < 80% (1.9 (1.0–3.0) % vs 1.7 (0.8–2.6) %; ns). In total, 186 ABCs with oxygen therapy before and 168 ABCs after training and guideline implementation occurred. The duration of SpO(2) < 80% reduced (2 (1–2) vs 1 (1–2) minutes; p < 0.05), the occurrence of SpO(2) > 95% did not decrease (73% vs 64%; ns) but lasted shorter (2 (0–7) vs 1 (1–3) minute; p < 0.004). Conclusion: Training and guideline implementation in manual oxygen titration improved SpO(2) targeting in preterm infants with more time spent within the target range and less frequent hyperoxaemia. The durations of hypoxaemia and hyperoxaemia during ABCs were shorter.